(untitled) (Journal of Nobel Medical College, 2018)
Background: Clean and safe water is one of the basic needs of human beings. Inaccessibility to this and poor sanitation leads to various water borne diseases, gastro enteropathy and under nutrition. In Nepal, only 39% of total population have access to improved sanitation and 38.4% of people defecate in open airs. So the objective of this study was to assess the level of knowledgeand practices regarding safe drinking water and sanitation among women. Materials and methods: A descript cross-sectional research design was adopted for the study. A convenient sampling technique was used for sample collection. A self-designed structured questionnaire along with face to face interview was to evaluate the knowledge. Data were analysed by using descriptive as well as inferential statistics to find out association betweenlevels of knowledge of safe drinking water. Result: The findings showed that among 75 participants, 44% had adequate knowledge, 45.3% had moderate knowledge and 10.7% had inadequate knowledge regarding safe water and sanitation. In this study most ofthe respondents,ie 45.3% had moderate knowledge. Conclusion: The research findings concluded that most of the participants had moderate knowledge about safe drinkingwater and sanitation. Thus, the author feels community mass health education is required in this community to prevent water borne diseases.